MANAJEMEN MEDIA SOSIAL DALAM MANAJEMEN SEKOLAH: ANALISIS KUANTITATIF PENGARUH INSTAGRAM TERHADAP EFEKTIVITAS PPDB - Rani Supriyati Anwar; Ahmad Aziz Faozi (STKIP Pesisir Selatan, 2026)
This study examines the effect of Instagram social media management on the effectiveness of new student admissions (PPDB) at SMA Pramita Tangerang. A quantitative correlational approach with a cross-sectional design was applied to 55 respondents selected from 125 tenth-grade students using Slovin’s formula and simple random sampling. Data were collected through a closed Likert-scale questionnaire, then tested for item validity and internal reliability before further analysis. Instagram management was measured using the AISAS dimensions, namely attention, interest, search, action, and share, while PPDB effectiveness was assessed through indicators in the research instrument. Data analysis was conducted with IBM SPSS using descriptive statistics, Pearson correlation, and simple linear regression. The findings show a very strong and significant positive relationship between Instagram management and PPDB effectiveness (r=0.893; p<0.001; B=0.763; t=14.460; p<0.001), with an explanatory contribution of 79.8% (R²=0.798). The study’s novelty lies in positioning AISAS-based Instagram governance as a measurable school-management practice that supports admissions performance. These results provide empirical guidance for improving content planning, interaction quality, and account management in schools.